Dampak Kebakaran Lahan Gambut terhadap Perekonomian Masyarakat di Kecamatan Gambut Kabupaten Banjar - R Rosyida; Yunita Sopiana (PPJP Universitas Lambung Mangkurat, 2021)
This research was conducted to find out: (1) to find out how the impact of land fires on the economy of the community in the Gambut District of Banjar Regency before the occurrence of land fires (2) to find out how the impact of the land fires on the economy of the community in the Gambut District of Banjar Regency after the land fires. The respondents of this study were 87 community heads of households residing in Gambut Village, Banjar Regency. This research is a qualitative descriptive study. Data collection methods used were interviews (in-depth interviews and questionnaires), observation, documentation, and literature study. The results of this study indicate that the impact of land fires greatly influences the economy of the community in Gambut District, Banjar Regency. Land area (X1), income (X6) and occupation (X7) variables are the most dominant influences on the community's economy in the Gambut District, Banjar Regency.